256 Relationship between balance and lower extremity ROM, H/Q ratio, hamstring tightness, beighton score in professional folk dancers and professional football players. (3rd March 2020) - Akgonul, Busra; Atansay, Vefa; Kara, Ayhan Nedim; Hamzaoglu, Azmi; Aksu, Neslihan
Abstract : Background: One of the factors of performance is to be agile that would require combination of speed, balance, power and coordination. Balance analysis is often used as an indication of risk of frequent injuries. In most of the sports, proprioceptive education programs are adapted to prevent lower extremity functional injuries. Objective: We aimed to determine the difference in balance between professional dancers and professional footballers and its relationship with lower extremity ROM, muscle strength (hip abductor- adductor, quadriceps, hamstring), H/Q ratio, hamstring tightness (Sit and reach, Straight Leg Raise (SLR) test), hypermobility test (Beighton score). Design: Prospective comparative study. Setting: Professional folk dancers (Fire of Anatolia Dance Group) and Premier League football players. Patients (or Participants): Volunteered 20 professional folk dancers and 20 Premier League football players Interventions (or assessment of risk factors): Hamstring tightness, decreased ROM, Beighton score (smaller or equal of 3, greater or equal of 5) is the risk factor for static and dynamic balance decrease. Main outcome measurements: SportKAT 4000 (Kinesthetic Ability Trainer) measurements (p<0, 005) are better in dancers (eyes open with both feet, right leg only, left leg only, eyes closed both feet, eyes open dynamic both feet) compare to athletes.Active ROM angles (p<0, 005) are significantly higher in dancers' hip, knee and ankle compare to athletes. Our findings showed that dancers' Beington score was 3, 8±3 and athletes' score was 2, 5±1, 5. Hamstring lenght in dancers was 95, 5±10 and athletes was 76, 6±7, 1. Results: Dancers' static and dynamic balances (p<0, 005) are significantly better than athletes. H/Q ratios are not different between dancers and athletes; however, dancers' Hamstring length (p<0, 005) is higher compare to athletes. Conclusions: Decreased flexibility and ROM cause lesser resistance to perturbation and balance problems. We think that dancer are better in static and dynamic balances compare to athletes due to greater ROM degrees and Hamstring flexibility.